2010
DOI: 10.1159/000314900
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Large Granular Lymphocytic Leukemia in Association with Sjögren’s Syndrome

Abstract: T cell large granular lymphocytic (LGL) leukemia is a rare condition accounting for 2–3% of all mature lymphoid leukemias. Here, we present the case of a 73-year-old woman presenting with neutropenia and anemia (hemoglobin 9.9 g/dl). Hematological assessment revealed the presence of a T cell LGL leukemia. At the time of T cell LGL leukemia diagnosis, the patient developed xerophthalmia and xerostomia, and a diagnosis of Sjögren’s syndrome was made following salivary gland biopsy. The finding of large granular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…With regards to the former, one hypothesis which has already been proposed [ 10 ] is that the continuous immune stimulation enabled a mutated clone to develop and lose its typical high turnover rate. In line with this hypothesis, therapy aimed at immune system control would lead to lymphocyte count normalization [ 7 , 8 ]; indeed, our patient was managed with immunosuppressive therapy and is still in good health, with a good lymphocytosis control even years later.…”
Section: Discussionsupporting
confidence: 59%
“…With regards to the former, one hypothesis which has already been proposed [ 10 ] is that the continuous immune stimulation enabled a mutated clone to develop and lose its typical high turnover rate. In line with this hypothesis, therapy aimed at immune system control would lead to lymphocyte count normalization [ 7 , 8 ]; indeed, our patient was managed with immunosuppressive therapy and is still in good health, with a good lymphocytosis control even years later.…”
Section: Discussionsupporting
confidence: 59%
“…Perhaps not coincidentally, T‐LGLL is also reported in pSS, with subsequent reports suggesting an association with rheumatoid factor in autoimmune diseases . Twelve of 48 patients with T‐LGLL evaluated were diagnosed with pSS; cytokine production by neoplastic cells was proposed to lead to autoimmune disease.…”
Section: Discussionmentioning
confidence: 89%
“…Surprisingly, Friedman et al, in a cohort of 13 patients with SS-associated T-LGL leukemia, observed clonal dominant expansion of CD4+ T-lymphocytes in 4 (31%) patients [ 24 ]. Moreover, out of five patients with pSS-associated T-LGL leukemia, four patients had the typical CD8+ phenotype [ 25 , 27 , 28 ], and in one patient T-LGLs coexpressed CD4 and CD8 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the first description of SS with LGL leukemia was presented by Goske et al (1980), who reported on a 52-year-old woman with SS, absolute lymphocytosis, and neutropenia [18]. We found only 39 cases of T-LGL leukemia in SS patients in PubMed to date [7,[19][20][21][22][23][24][25][26][27][28]. Of these, 31 cases of T-LGL leukemia were associated with pSS, 2 cases with sSS (one patient had RA and another had limited scleroderma), and in 6 cases, no information was provided.…”
Section: Discussionmentioning
confidence: 99%